Effect of Burnout and Work-Life Balance on Psychological Well-Being in Full-Time Working Women - Putri, Islamidiena Dheananda; Nugrahany, Widuri; Puspitawati, Ira (Universitas Negeri Malang, 2024)
In recent decades, working women’s social and economic reality has significantly transformed. Not only contributing to the household but having an important role in the world of work in various professional sectors. This research examines the influence of burnout and work-life balance on psychological well-being in full-time working women. This research uses multiple linear regression analysis as a quantitative method. The sample of this research was 103 full-time working women using a purposive sampling technique. The instruments used were the Maslach Burnout Inventory (MBI), the work-life balance scale, and the psychological well-being scale. The results of the data analysis show that burnout can negatively affect psychological well-being in full-time working women, and work-life balance can positively affect psychological well-being in full-time working women. Then, burnout and work-life balance affect the psychological well-being of full-time working women simultaneously with a significant influence (R-squared) of .604, which means that the burnout and work-life balance variables influence 60.4% on psychological well-being and other variables influence the remaining 39.6%.